2019
DOI: 10.1017/s0022215119001269
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of round window niche accessibility pre-operatively on high-resolution computed tomography of the temporal bone with intra-operative findings

Abstract: ObjectiveTo compare round window niche visibility as seen endoscopically during cochlear implant surgery with pre-operative high-resolution computed tomography of the temporal bone.MethodsNineteen patients scheduled for cochlear implantation, aged 2–20 years, were referred for computed tomography from October 2016 to March 2018. Angles were measured between the lines passing through the mid-sagittal plane and cochlear basal turn on the scans. Endoscopic round window niche visibility during posterior tympanotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Endoscopic Cochlear Implantation Cochlear implantation is one of the new applications of endoscopes in the field of otology, but there are few case series on this topic. In a recent study, Sharma et al 28 concluded that the visualization of the round window niche improved with the use of an otoendoscope with 1.9 mm in diameter for cochleostomy and insertion of the electrode; a similar conclusion was reached in the study by Jain A et al 29…”
Section: The Ability To Visualize Past the Shaft Of Larger Surgicalmentioning
confidence: 60%
“…Endoscopic Cochlear Implantation Cochlear implantation is one of the new applications of endoscopes in the field of otology, but there are few case series on this topic. In a recent study, Sharma et al 28 concluded that the visualization of the round window niche improved with the use of an otoendoscope with 1.9 mm in diameter for cochleostomy and insertion of the electrode; a similar conclusion was reached in the study by Jain A et al 29…”
Section: The Ability To Visualize Past the Shaft Of Larger Surgicalmentioning
confidence: 60%
“…How can we evaluate RWNV by noninvasive measurement? Previous inner ear imaging studies mostly focused on the measurement of the round window niche (RWN) and its position relationship with adjacent structures (such as the cochlear basal turn and facial nerve) to assess its impact on cochlear implantation, [18][19][20][21][22][23][24][25] but little attention had been paid to the existence of RWNV and its possible clinical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pathologies of the middle and inner ear, such as malformations, inflammation, trauma and especially cancer can be assessed precisely for preoperative planning [1]. High positive and negative predictive values of up to 91% for intraoperative findings involving middle ear structures-i.e., ossicles or the round window-as well as the extent of cholesteatoma and neoplasms have been described in earlier studies on high-resolution CTs of the temporal bone [2][3][4][5]. Otologic surgeons, therefore, prefer high-resolution CTs to avoid image noise and the blurred visualization of subtle temporal bone structures.…”
Section: Introductionmentioning
confidence: 99%